Moral Crisis and Confucian Resurrection: New Three-Word Classic in China / Crisis moral y resurrección del confucionismo: nuevo Clásico de las Tres Palabras en China - Chan, Kin-man (Araucaria, 2016)
The transition from state socialism to market socialism in China since 1978 led to a sense of disorientation and moral crisis in the Chinese population which by the mid-1990s the Chinese Communist Party (CCP) attempted to correct. Specifically, the CCP Committee in the region of Guangdong responded by elaborating a new version of the teaching manual Three-Word Classic in order to meet the new social circumstances with a body of specific moral rules based on Confucian philosophy and aimed at the Chinese younger generations. The Party’s chief goal was to rebuild the framework of moral behavior ousted by the rapid social changes of the 80s and 90s and which until the reform era was supplied by the official line of the CCP and the ideas nurtured during the Cultural Revolution. The New Three-Word Classic soon became widely popular in the country and allowed schools to teach their students a series of moral rules through the examples of historical figures and events which overall championed patriotism and diligence in learning but failed to address public spiritedness, essential in guiding emerging public life in China.